Pentingnya Islam dalam Pendidikan Anak ditingkat Sekolah Dasar (Indo-MathEdu Intellectuals Journal, 2024)
Islamic education for children requires the integration of religious values ​​in the curriculum and the active role of families and teachers. This study aims to evaluate the role of teachers and parents in conveying and implementing Islamic values ​​and analyzing the impact of heredity and environmental factors on child development. Qualitative methods with thematic analysis techniques were used to evaluate related literature. The results showed that teachers act as knowledge transmitters, skills trainers, directors, and mentors, while parents educate through behavioral examples, early education systems, habits, and dialogue culture. Heredity and environmental factors also contribute significantly to child development. In conclusion, the integration of religious values, the role of effective teachers, and family support are essential to ensure the development of children's character as a whole, with attention to the significant influence of heredity and environment